Advances in Plant-Hemipteran Interactions - Linda Walling (Frontiers Research Topics, 2017)
Hemipterans encompass a large group of insect pests of plants that utilize mouthparts which are modified for piercing and consuming fluids from plants. In addition, hemipterans vector viral and bacterial diseases of plants. This book brings together a set of reviews and research papers that showcase the the range of activities being undertaken to advance our understanding of the multi-organismal interaction between plant, hemipterans and microbes.